The Role of Local Self-Government Bodies in the Social Protection System of Population in RА - Vardanyan, Yevgine (Journal of Sociology: Bulletin of Yerevan University, 2014)
The development of local selfgovernment system in Armenia created necessary bases for the decentralization of authority. Today the necessity of further recession of the decentralization is obvious and demands to take appropriate actions for successful realization of that goal. The socialeconomical difficult situation which we have in our country creates the necessity of recession of decentralization also in the social protection sphere of population and in the expansion of the authorities of local self-government bodies in that sphere as well. The necessity of the expansion of the authorities of the local self-government bodies in Armenia, the opportunities which we have and the perspectives which we can see for that, are discussed in this article.
Keywords: decentralization, local self -government, authorities of local self-government bodies, social protection of population, social work, territorial agencies of social services